Hacking WEP/WPA/WPA2 Wi-Fi networks using Kali Linux (Packt Publishing, 2022)
Learn to secure and crack WEP/WPA/WPA2 key and perform MITM attack from scratch using Kali Linux About This Video Detect ARP Poisoning (MITM) attack to protect yourself against it Crack any Wi-Fi encryption using several methods Understand how to hack the connected clients In Detail In this course, you will learn how to set up your Kali Linux lab environment properly. In addition to that, you will learn how devices communicate with each other. Lastly, you will learn the best out of this course, which is the Man in the Middle attacks. This course is divided into six sections: - Preparation: In this section, you will learn how to download and set up the latest version of Kali Linux as a virtual machine or as your main OS. This helps you create your own safe hacking lab environment. - Network basics: Here you will learn the basics of networks that will help you understand what should be done before network security testing. - Gather AP information before cracking: In this section, you will learn how you can enumerate the target access point such as ESSID-BSSID-Channel-Encryption type, and so on. You will learn how you can disconnect, kick any client from your target network, or even jam the wireless access point completely without having its password. - Cracking WEP/WPA/WPA2 encryption: After gathering information about the target access point, it's time to learn how to crack WEP/WPA/WPA2 encryption keys and the theory behind each attack. - MITM attack: In this section, you will learn how to perform man-in-the-middle attacks and what post-modules can be carried out on the target OS. Modules such as playing music on the target OS, stealing credentials, and many more. You will even learn how to gain full access to the connected devices. Protecting yourself against these attacks: After learning MITM attacks, it's time to learn how to protect your OS against all the previously mentioned attacks. By the end of the course, you will be able to perform a MITM attack on the target network and fully control all the connected computers. You will be able to protect yourself from the MITM attack. Audience This course is intended for beginners and professionals. If you are a beginner, you will start from scratch until you become a professional, and if you are a professional, this course will enhance and refresh your knowledge about wireless network hacking. This course is for people who want to do penetration testing against a specific Wi-Fi network.